KARAKTERISASI MORFOLOGI DAN ANATOMI ISOLAT RHIZOCTONIA MIKORIZA ANGGREK VANDA LIMBATA - WAHYU DWIYANTO; R. Soelistijono; DWI SUSILO UTAMI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2017)
Rhizoctonia mycorrhizal fungi is a group that has a very important role for the plant anggrekan. Endophyte orchid belonging to the genus Rhizoctonia that consists of three species, namely R. repens, mucoroides R., and R. lanuginose. Rhizoctonia fungus colony morphology sp. contained in preparations or isolates no difference because the preparations are equally white as found in isolates. Different characteristics of the mycorrhizal Rhizoctonia root Vanda limbata Flores seen by colony color hyphae, and the number of cell nuclei. Rhizoctonia mycorrhizal hyphae colonies on the roots of the orchid Vanda limbata has mycelium is brown, there are barriers hyphae (septa) therein, and some have 2 cell nucleus. Mycelium Rhizoctonia sp. in isolates Vanda limbata is large While colonies hyphae Rhizoctonia sp. in isolates Vanda limbata known paler brown, do not have septa, and has a core of more than 1. The mycelium Rhizoctonia sp. on the roots of Vanda limbata which tend to tan and smaller. It can be said mycorrhizal Rhizoctonia contained in Vanda limbata included in binukleat like R. repens group that includes orchid mycorrhizal fungi. While mycorrhizal Rhizoctonia contained in Vanda limbata including nature groups such multinucleate R. solani, T. cucumeris, T. pennatus contained orchids. Binukleat or multinucleate Rhizoctonia group as good because it is as mycorrhizae